Взаимодействие РНК-полимеразы Escherichia coli с ДНК-подобными дуплексами, содержащими повторы. Влияние последовательности нуклеотидов - Королева, О.Н.; Друца, В.Л.; Шабарова, З.А. (Биополимеры и клетка, 1988)
Изучено взаимодействие РНК-полимеразы Е. coli с шестью типами синтетических двуспиральных полинуклеотидов, содержащих декануклеотид- ные повторы. Показано, что полимеры, содержащие в своей структуре последовательность TATA – Т, обладают промотороподобными свойствами: образуют устойчивые к гепарину транскрипционно активные комплексы с ферментом. Вивчено взаємодію РНК-полімерази Е. coli з шістьма типами синтетичних двоспіральної полинуклеотидов, містять декануклеотід-ні повтори. Показано, що полімери, що містять у своїй структурі послідовність TATA-Т, володіють промотороподобнимі властивостями: утворюють стійкі до гепарину транскрипційно активні комплекси з ферментом. The chemical-enzymatic synthesis of DNA-duplexes d(pCATTATAATG)n (I), d(pGATTATAATC)n (II), d(pCTTTATAAAG)n (III), d(pCATTTAAATG)n (IV), d(pCAATATATTG)n (V), d(pCATAATTATG)n (VI) (n= 104-20), containing repeats of the sequences completely and partially homologous to the «ideal» Pribnow box (TATAATG) has been carried out. The binding of E. coli RNA polymerase to synthetic DNA duplexes and in vitro transcription of these duplexes have been studied. It has been shown that duplexes I, II and V containing the sequence TATA-T form heparin-resistant Uanscriptionally active complexes with enzyme (the half life is ~ 100-200 min) while duplexes III and IV do not form stable complexes. The pnedominant in vitro transcription initiation sites were revealed within duplexes I, II and VI.